Examining the Impact of Supply Chain Technology Implementations on Supply Chain Effectiveness and Firm Value - Detro, Jonah (Digital Repository of Theses - SSBM Geneva, 2024)
In the contemporary business environment, the drive towards efficiency, agility, and innovation ever intensifies. Pivotal to this transformation is the integration of Supply Chain Technology (SCT), which promises to overhaul traditional supply chain paradigms and revamp workforce dynamics and information flow. This research thesis, submitted to the Swiss School of Business and Management, delves deeply into the multifaceted ramifications of SCT implementations concerning supply chain proficiency and corporate valuation. Utilizing comparative analysis, this investigation merges qualitative insights with quantitative data, ensuring an exhaustive scrutiny of SCT's multifaceted applications. This holistic methodology not only assures research fidelity but also elevates the study's contribution to the existing body of knowledge on SCT. The curated case studies and samples span a wide range of implementation scenarios, while the data acquisition methods are adeptly tailored to discern the complex multivariate aspects of SCT, capturing both overarching and granular perspectives. The research revolves around three pivotal aims: crafting a robust theoretical construct on SCT integrations; empirically substantiating this framework through both numerical and narrative evidence; and transmuting these academic discoveries into pragmatic strategies. The primary aspiration is to elucidate the variety of factors that anchor the success or lead to the setback of SCT implementations. Such revelations are invaluable for industry decision makers and practitioners, particularly those at the decision-making levels mulling over SCT investments. The application of the evolved framework to tangible case studies reinforces its practical utility and versatility. The findings spotlight critical drivers of SCT implementation outcomes. Organizational agility and an adaptable culture stood out as cornerstone elements, with adaptive entities reporting higher SCT success rates. Integration complexities with legacy systems posed formidable challenges, accentuating the necessity for phased, strategic integrations. Emphasis was also placed on comprehensive stakeholder engagement and training, indicating that inclusive SCT adoption strategies yield superior results. The empirically validated framework offers businesses a pragmatic navigation tool in the SCT realm, bolstering their confidence in these undertakings. Thus, this thesis is a dual offering: a scholarly contribution and a strategic compass for enterprises navigating the SCT terrain in today's dynamic business topography.